Republic of Kiribati Early Childhood Development : SABER and NSA-ECD Country Report 2014 - World Bank Group (2016)
This report presents an analysis of the Early Childhood Development (ECD) subsector, including programs and policies that affect young children in the Republic of Kiribati. This was a collaborative effort between UNICEF and the World Bank Group; it combines the World Bank Group’s Systems Approach for Better Education Results SABER-ECD framework, which includes analysis of early learningand child p, health, nutrition, and social rotection policies and interventions in Kiribati, along with regional and international comparisons, as well as the regionally developed UNICEF National Situational Analysis ECD, which takes a greater in-depth look at the following system components, which have been highlighted by the Pacific Region as priority components for quality Early Childhood Care and Education (ECCE) implementation: policy, legislation, and governance; human resources; curriculum, child assessment, and environment; performance monitoring and assessment; and community partnerships. In 2008, the Ministry of Education (MOE) drafted the Kiribati Early Childhood Care and Education (ECCE) Policy, which was formally endorsed by Cabinet in 2010. The ECCE policy, targeting ages three to five, calls ECCE a “national responsibility” with a mission “to culturally nurture young children in a loving and caring environment to enhance through interactive play the fullest potential of their physical, intellectual, social, emotional and spiritual growth in line with trends and development”. This country report presents a framework to benchmark Kiribati’s ECD system; each of the nine policy levers and five system components are examined in detail, and policy options to strengthen ECD are offered. This report is intended to serve as a first step for decision making within the government of Kiribati to improve the ECD system. Now that some areas in need of policy attention have been identified, the country can move forward in prioritizing policy options to promote healthy and robust development for all children during their early years.